ERALab Sdn. Bhd. / Hasibah Naqibah Hasbullah - Hasbullah, Hasibah Naqibah (Faculty Of Chemical Engineering, 2022)
This report consists of student's Industrial Training course Diploma in Chemical Engineering (EHl 10) which has been carried out at a commercial lab, ERALab Sdn Bhd. The internship period is 24 weeks starting from 21 February to 4 August 2022. This course must be taken by all students from Diploma in Chemical Engineering in order to complete their studies. Students will be assigned to the company that they can be evaluate by the company supervisor and as well as the university's supervisor. Within practical training, students can utilize the time wisely to gain experience as much as possible and also apply the theoretical knowledge with real working condition. This report also covers every activity that has been carried in every unit, skills applied, special projects and all the task that students successfully perform during 6 months training in ERALab Sdn Bhd. Additionally, this report also contains background information of the company, details of training, experience gained and problem solving. The challenges and issues faced by student as well as suggestion for improvement during the training period has all been clearly mentioned. Besides, this report also included a brief description of the work that students had learned and performed.